Genomic insight into the population history and biological adaptations of high-altitude Tibetan highlanders in Nagqu - Ma, Lifeng; Wang, Rui; Feng, Siwei; Yang, Xiaomin; Li, Jing; Zhang, Zhiying; Zhan, Haoshuang; Wang, Yao; Xia, Ziyang; Wang, Chuan-Chao; Kang, Longli (Frontiers in Ecology and Evolution, 2022)
Tibetan, one of the largest indigenous populations living in the high-altitude region of the Tibetan Plateau (TP), has developed a suite of physiological adaptation strategies to cope with the extreme highland environment in TP. Here, we reported genome-wide SNP data from 48 Kham-speaking Nagqu Tibetans and analyzed it with published data from 1,067 individuals in 167 modern and ancient populations to characterize the detailed Tibetan subgroup history and population substructure. Overall, patterns of alleles sharing and haplotype sharing suggested (1) the relatively genetic homogeny between studied Nagqu Tibetans and ancient Nepalese as well as present-day core Tibetans from Lhasa, Nagqu, and Shigatse; (2) the close relationship between our studied Kham-speaking Nagqu Tibetans and Kham-speaking Chamdo Tibetans. The fitted qpAdm models showed that studied Nagqu Tibetans could be fitted as having the main ancestry from late Neolithic upper Yellow River millet farmers and deeply diverged lineages from Southern East Asians (represented by Upper Palaeolithic Guangxi_Longlin and Laos_Hoabinhian), and a non-neglectable western Steppe herders-related ancestry ( 3%). We further scanned the candidate genomic regions of natural selection for our newly generated Nagqu Tibetans and the published core Tibetans via FST, iHS, and XP-EHH tests. The genes overlapping with these regions were associated with essential human biological functions such as immune response, enzyme activity, signal transduction, skin development, and energy metabolism. Together, our results shed light on the admixture and evolutionary history of Nagqu Tibetan populations.